Renal Auto-Transplantation for Loin Pain Hematuria Syndrome Using a Multidisciplinary Team Model: Intermediate-Term Results - Campsen, Jeffrey (Cureus, 2020)
Background Patients with loin pain hematuria syndrome (LPHS) can find relief via multiple modalities, few provide long-term pain control like renal auto-transplantation (RAT). This study evaluates the intermediate effectiveness of the RAT procedure’s ability to achieve long-term pain control and quality of life improvement. Methods All patients with suspected LPHS were seen by a multi-disciplinary team (MDT) composed of urologists, interventional radiologists, and transplant surgeons. Clinical history and physical exam, lab values, imaging findings, and response to renal hilar block (RHB) were used to determine LPHS and candidacy for potential RAT. Preoperative, one-year, three-year, and five-year postoperative pain assessment scores and quality of life surveys were administered to each LPHS and potential RAT patient. Results Eighty-four LPHS patients were referred for the evaluation of and consultation for the option of RAT. Sixty-four of these patients underwent RHB of which 60 (93.8%) had a positive response, defined as a temporary reduction of pain score by >50%. Forty-six of the 60 patients who responded favorably proceeded to RAT. At the one-year follow-up, there was a 75% reduction in pain with 88.9% of patients experiencing a 50% reduction in pain. At one year, the mean Beck Depression Inventory (BDI) decreased by 65.4%, from an average of 23.7 to 8.2. Similarly, at three years (n = 5) and five years (n = 3), the mean pain scores were 2 and 1. Conclusions The MDT evaluation of potential LPHS patients with our protocol and treatment results in an improvement in pain and depression scores in these selected patients.